2005
DOI: 10.1172/jci25641
|View full text |Cite
|
Sign up to set email alerts
|

cIAP2 is a ubiquitin protein ligase for BCL10 and is dysregulated in mucosa-associated lymphoid tissue lymphomas

Abstract: The pathogenesis of mucosa-associated lymphoid tissue (MALT) lymphomas is associated with independent chromosomal translocations that lead to the upregulation of either BCL10 or MALT1 or the generation of a fusion protein, cIAP2-MALT1. While both BCL10 and MALT1 are critically involved in antigen receptormediated NF-κB activation, the role of cIAP2 is not clear. Here we show that cIAP2 is a ubiquitin ligase (E3) of BCL10 and targets it for degradation, inhibiting antigen receptor-mediated cytokine production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 39 publications
6
116
1
Order By: Relevance
“…Rather, our data suggest that API2(1-441) slightly enhances Bcl10-mediated and CARMA1-mediated NF-kB activation. This finding is consistent with a recent report in which Hu et al (2006) proposed that the binding of Bcl10 to the BIR region of wild-type API2 leads to Bcl10 ubiquitination and degradation. According to this model, API2(1-441) could competitively inhibit Bcl10 interaction with wildtype API2.…”
Section: Loss Of Api2-malt1-dependent Nf-kb Activity Occurs If Oligomsupporting
confidence: 93%
See 2 more Smart Citations
“…Rather, our data suggest that API2(1-441) slightly enhances Bcl10-mediated and CARMA1-mediated NF-kB activation. This finding is consistent with a recent report in which Hu et al (2006) proposed that the binding of Bcl10 to the BIR region of wild-type API2 leads to Bcl10 ubiquitination and degradation. According to this model, API2(1-441) could competitively inhibit Bcl10 interaction with wildtype API2.…”
Section: Loss Of Api2-malt1-dependent Nf-kb Activity Occurs If Oligomsupporting
confidence: 93%
“…For example, a recent report suggested that the BIR1 domain of API2 might contribute to API2-MALT1-dependent NF-kB activation by promoting association of the fusion protein with membrane lipid rafts (Baens et al, 2006). Another recent report demonstrated that the API2 BIR1 interacts with Bcl10 (Hu et al, 2006). These authors suggested that binding of API2-MALT1 to Bcl10 may promote lymphocyte proliferation by protecting Bcl10 from wild-type API2-mediated ubiquitination and degradation (Hu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to apoptosis accompanied by uncontrollable cell division could promote growth of tumor mass in the nude mice. This working model is also supported by the knowledge that a G 2 /M checkpoint defect promotes tumorigenesis (3) and that there is close association of up-regulation of three such antiapoptotic proteins, Bcl-xL, XIAP, and cIAP2, with constitutive activation of NF-B and resistance to apoptosis in a variety of human malignancies (45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 82%
“…27 Hosokawa et al 57 failed to demonstrate an interaction with endogenous BCL10, possibly because their fusion variant contained only the second Ig domain of MALT1 which might not be sufficient to engage BCL10. But Hu et al 58 showed that overexpressed BCL10 interacts with the BIR domains of the API2-MALT1 fusion, and RNA-mediated interference experiments further indicated that BCL10, at least in HeLa cells, is crucial for API2-MALT1 to activate NF-kB. These discrepancies might rise from the kind of API2-MALT1 fusion variant used, the cell systems in which the experiments were performed and the BCL10 expression level (endogenous or overexpressed) and demand clarification.…”
Section: Pathogenesis Of Malt Lymphomasmentioning
confidence: 99%